Coronal Imbalance after Selective Posterior Thoracic Fusion in Patients with Lenke 1 and 2 Adolescent Idiopathic Scoliosis. (9th December 2018) - Jiang, Heng; Shao, Wei; Xu, Enjie; Ji, Zhe; Lin, Tao; Meng, Yichen; Ma, Jun; Wang, Ce; Gao, Rui; Zhou, Xuhui
Abstract : Coronal decompensation is a common complication in Lenke 1 or 2 AIS patients after selective thoracic fusion (STF). However, the majority who developed immediately postoperative coronal decompensation experienced improvement and the related factors are not fully understood. The aim of this retrospective study was to investigate the prevalence of coronal imbalance in patients with Lenke 1 or 2 AIS and to explore radiological factors associated with spontaneous correction of coronal balance after surgery. Lenke 1 or 2 AIS patients receiving STF in our center from January 2013 to March 2015 were analyzed. Anteroposterior and lateral films were evaluated before surgery, at 1 month's and 2 years' follow-up. Patients were divided into 2 groups according to whether coronal imbalance occurred in the early postoperative period (1 month). Various radiological parameters as well as Scoliosis Research Society-22 were statistically compared between groups. Coronal decompensation was observed in 33 patients preoperatively, in 48 patients immediately postoperatively, and in 2 patients at final follow-up. Lowermost instrumented vertebra (LIV) disc angle (0.9° vs. 6.7°, p=0.019) and LIV- C7 plumb line and central sacral vertical line (CSVL) (-3.4mm vs. -13.7mm, p=0.020) increased in the final follow-up in the imbalanced group of type A modifier. The magnitude of lumbar curve was greater in the imbalanced group of type B or C modifier in the early postoperative period (19.5° vs. 12.6°, p=0.006; 25.5° vs. 13.7°, p<0.01), and this difference disappeared in the final follow-up. No differences in SRS-22 outcome scores were noted between groups in different time. Coronal imbalance was frequently detected immediately after STF in Lenke 1 or 2 AIS patients, with type C modifier slightly higher than A or B. Distal adding-on may help compensate for coronal imbalance in patients with type A modifier, while spontaneous correction of lumbar curve attributes to the improvement of coronal imbalance in patients with type B or C modifier.